Fontes e doses de fósforo na presença e ausência de composto orgânico no estado nutricional e na produtividade da cana-de-açúcar - Moda, Leandro Rosatto [UNESP] (2014)
The filter cake application associated with phosphate fertilizer can prevent the adsorption of phosphorus in soil colloids. The objective of this research was to evaluate the effect of application of rates of phosphorus on different sources, in the presence and absence of filter cake on growth, nutritional status and productivity of cane plant and first ratoon, grown in different soils in State of São Paulo, harvested without straw removal by burning. Two experiments were conducted in 2012/2013 and 2013/2014 cropping seasons in Kandiudalf and Haplustox soils in São Paulo, Brazil. The experimental design was a randomized block in a 3x4x2 factorial arrangement with three sources of phosphorus (Phosphate of Araxá, Gafsa phosphate and triple superphosphate) and four rates of P [zero (control); 90; 180 and 360 kg ha-1 of P2O5] in the presence and absence of 7.5 t ha-1 of filter cake (dry basis), with three replicates. Were evaluated the availability of soil P (P-resina, P-remanescente), the nutritional status of P in the leaves (at 120 and 240 days after planting and through alternative method determining the activity of leaf acid phosphatase) the yield of straw and stalks, phosphorus accumulation by plants and the technological quality of the sugarcane juice. The application of phosphorus levels increased the nutrient content in the soil, when associated with the filter cake improved the growth of sugarcane, and the phosphorus nutrition, increasing sugarcane yield. Leaf analysis was efficient in the two sampling periods, however, the phosphatase activity was not important to predispose the nutritional status of P. The effects of the treatments were similar in the different soils, however, in Kandiudalf the yield was higher that in Haplustox soil. In Kandiudalf the Gafsa phosphate promoted increase in stalk production in first year compared to other sources, reaching 214 t ha-1 with 209 kg ha-1 P2O5, triple superphosphate promoted ...